Next-Generation Cancer Immunotherapy Targeting Glypican-3 - Shimizu, Yasuhiro; Suzuki, Toshihiro; Yoshikawa, Toshiaki; Endo, Itaru; Nakatsura, Tetsuya (Frontiers in Oncology, 2019)
Glypican-3 (GPC3), a 65 kD protein consisting of 580 amino acids, is a heparan sulfate proteoglycan bound to the cell membrane by glycosylphosphatidylinositol. This protein is expressed in the liver and the kidney of healthy fetuses but is hardly expressed in adults, except in the placenta. Contrarily, GPC3 is specifically expressed in hepatocellular carcinoma (HCC), ovarian clear cell carcinoma, melanoma, squamous cell carcinoma of the lung, hepatoblastoma, nephroblastoma (Wilms tumor), yolk sac tumor, and some pediatric cancers. Although the precise function of GPC3 remains unclear, it has been strongly suggested that it is related to the malignant transformation of HCC. We identified GPC3 as a promising target for cancer immunotherapy and have been working on the development of cancer immunotherapeutic agents targeting it through clinical trials. In some trials, it was revealed that the GPC3 peptide vaccines we developed using human leukocyte antigen-A24- and A2-restricted GPC3-derived peptides could induce GPC3-specific cytotoxic T cells in most vaccinated patients and thereby improve their prognosis. To further improve the clinical efficacy of cancer immunotherapy targeting GPC3, we are also developing next-generation therapeutic strategies using T cells engineered to express antigen-specific T-cell receptor or chimeric antigen receptor. In addition, we have successfully monitored the levels of serum full-length GPC3 protein, which is somehow secreted in the blood. The utility of GPC3 as a biomarker for predicting tumor recurrence and treatment efficacy is now being considered. In this review article, we summarize the results of clinical trials carried out by our team and describe the novel agent targeting the cancer-specific shared antigen, GPC3.